2019
DOI: 10.1101/843797
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Muscle synergies are associated with intermuscular coherence in an isometric upper limb task

Abstract: To elucidate the underlying physiological mechanism of muscle synergies, we investigated the functional corticomuscular and intermuscular binding during an isometric upper limb task in 14 healthy participants. Cortical activity was recorded using 32-channel encephalography (EEG) and muscle activity using 16-channel electromyography (EMG). Using non-negative matrix factorization (NMF), we calculated muscle synergies from two different tasks. A preliminary multidirectional task was used to identify synergy prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Isometric tasks have been studied in motor control from a muscle synergy perspective, and these studies have demonstrated that different isometric motor behaviors can be accomplished by activating a small number of intermuscular patterns in the upper body ( Rashedi et al, 2010 ; Borzelli et al, 2012 , 2013 ; Berger and d’Avella, 2014 ; Budhota et al, 2017 ; Ortega-auriol et al, 2019 ; Roh et al, 2019 ). For instance, four to five synergies were required to predict upper extremity muscle activation across different spatial, load, and position protocols ( Roh et al, 2012 ), and during visuomotor adaptation ( Gentner et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Isometric tasks have been studied in motor control from a muscle synergy perspective, and these studies have demonstrated that different isometric motor behaviors can be accomplished by activating a small number of intermuscular patterns in the upper body ( Rashedi et al, 2010 ; Borzelli et al, 2012 , 2013 ; Berger and d’Avella, 2014 ; Budhota et al, 2017 ; Ortega-auriol et al, 2019 ; Roh et al, 2019 ). For instance, four to five synergies were required to predict upper extremity muscle activation across different spatial, load, and position protocols ( Roh et al, 2012 ), and during visuomotor adaptation ( Gentner et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%